A Preliminary Stage of Supply Chain Strategy: Selection Qualified Catfish Seed - Phong Thanh Nguyen; Quyen Le Hoang Thuy To Nguyen; Andino Maseleno; Wahidah Hashim; Rais Zulkarnain; Tri Susilowati; Vy Dang Bich Huynh; Ngoc Bich Vu; Loan Phuc Le; Khoa Dang Vo; Phuong Thanh Phan (International Journal of Supply Chain Management, 2019)
Catfish is one of the freshwater fish that can be maintained in the pond yard of the house or in the field. The growth of catfish is quite fast with high durability and easy to breed in various maintenance locations. This fish is one type of fish consumption that is enough in the know and in the interest in Indonesia. A lot of people who want to cultivate these fish and want to get qualified catfish seed. For that in deciding determination of qualified catfish seed is needed for the continuity of breeding, to select the qualitfied catfish seed is needed some methods, one of the decision support system in selecting qualitfied catfish seed use SAW (simple additive weighting) method and efficient in the problems faced in this case study in order to obtain the high weight of various criteria that have been determined on the design process of decision support system. Benefits that can be obtained from using SAW method is to select and to decide for obtaning qualified fish seed without using too complicated ways.